Tunable passively Q-switched ytterbium-doped fiber laser with mechanically exfoliated GaSe saturable absorber - Ahmad, Harith; Aidit, Siti Nabila; Ooi, Shok Ing; Tiu, Zian Cheak (Chinese Laser Press, 2018)
A tunable passively Q-switched ytterbium-doped fiber laser using few-layer gallium selenide (GaSe) as a saturable absorber (SA) is demonstrated. The few-layer GaSe SA, which is fabricated by the mechanical exfoliation method, is able to generate a Q-switched fiber laser that has a maximum repetition rate of 92.6 kHz and a minimum pulsed width of 2.3 μs. The highest pulse energy exhibited by the generated pulse is 18.8 nJ with a signal to noise ratio of ∼40 dB. The tunability of the proposed laser covers from 1042 to 1082 nm, giving a tuning range of 40 nm.